Analytical Appraisal of Major Components of Public Speaking - Saleem Dhobi (Journal of Population and Development, 2026)
This paper appraises the key components of public speaking such as organization of the speech, confidence boosters, audience types, non-verbal language, overcoming stage fear, audience engagement approach and paralanguage. The objective of the paper is to demonstrate the impact of key components on public oration. How technical and thematic aspects of public speech can influence the effectiveness of the delivery is the inquiry question in the study. Public speaking is a fundamental communication skill that influences academic, professional, and social success. This paper analytically appraises the major components of public speaking, including content organization, verbal delivery, non-verbal communication, audience engagement, and psychological preparedness. Drawing on theories from Communication Studies and empirical research, the study examines how these components interact to produce effective speech outcomes. The paper adopts a qualitative analytical approach based on existing literature and highlights the importance of integrating cognitive, emotional, and behavioral elements in public speaking. The findings suggest that successful public speaking is not dependent on a single factor but rather on the balanced coordination of multiple components. The study contributes to pedagogy and training by offering insights into improving public speaking competence.